2016
DOI: 10.1002/prot.25197
|View full text |Cite
|
Sign up to set email alerts
|

Open and compressed conformations of Francisella tularensis ClpP

Abstract: Caseinolytic proteases are large oligomeric assemblies responsible for maintaining protein homeostasis in bacteria and in so doing influence a wide range of biological processes. The functional assembly involves three chaperones together with the oligomeric caseinolytic protease catalytic subunit P (ClpP). This protease represents a potential target for therapeutic intervention in pathogenic bacteria. Here, we detail an efficient protocol for production of recombinant ClpP from Francisella tularensis, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…It has been shown that ClpP, while maintaining its tetradecameric architecture, can assume several conformations that mainly differ in the height of its barrellike structure and in the conformation of the handle domain (11,67). High-resolution ClpP structures from various species include an active extended conformation with a fully formed catalytic triad and handle domain (38,68) as well as compressed/compact forms with kinked/truncated handle helices and unstructured handle β-sheets with misaligned active site residues (69)(70)(71)(72). While it is widely accepted that the extended form is prevalent in solution and is the active state, it has yet to be established whether the compressed/compact forms can be populated under conditions that are distinct from those used for crystallization, where crystal contacts can affect the ClpP structure (11,73).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that ClpP, while maintaining its tetradecameric architecture, can assume several conformations that mainly differ in the height of its barrellike structure and in the conformation of the handle domain (11,67). High-resolution ClpP structures from various species include an active extended conformation with a fully formed catalytic triad and handle domain (38,68) as well as compressed/compact forms with kinked/truncated handle helices and unstructured handle β-sheets with misaligned active site residues (69)(70)(71)(72). While it is widely accepted that the extended form is prevalent in solution and is the active state, it has yet to be established whether the compressed/compact forms can be populated under conditions that are distinct from those used for crystallization, where crystal contacts can affect the ClpP structure (11,73).…”
Section: Discussionmentioning
confidence: 99%
“…There is significant evidence from a variety of different biophysical techniques that ClpP is a highly dynamic molecular complex. For example, ClpP can be crystallized in three distinct conformations (4), including extended (25,26,31), compact (32,33), and compressed (31,34,35) forms that differ in the height of the barrel and in the conformation of the handle region. Further insight comes from NMR studies focusing on a pair of Ile residue probes showing the presence of at least two handle-region conformations in solution (36).…”
Section: Significancementioning
confidence: 99%
“…It has been shown that ClpP, while maintaining its tetradecameric architecture, can assume several conformations that mainly differ in the height of its barrel-like structure and in the conformation of the handle domain (11,67). High-resolution ClpP structures from various species include an active extended conformation with a fully formed catalytic triad and handle domain (38,68), as well as compressed/compact forms with kinked/truncated handle helices and unstructured handle β-sheets with misaligned active site residues (69)(70)(71)(72). While it is widely accepted that the extended form is prevalent in solution and is the active state, it is yet to be established whether the compressed/compact forms can be populated under conditions that are distinct from those used for crystallization, where crystal contacts can affect the ClpP structure (11,73).…”
Section: Discussionmentioning
confidence: 99%